LEARNING ELLIPTICAL SENTENCES THROUGH DIAGRAMMING BY THE ELEVENTH GRADE STUDENTS OF PEMBINA SENIOR HIGH SCHOOL OF PALEMBANG - Susi Aryanti (Esteem Journal of English Education Study Programme, 2019)
Abstract: The objective of this research was to find out it is effective learning elliptical sentences through diagramming by the eleventh grade students of the Pembina Senior High School of Palembang.The population of this investigation was all of the eleventh grades students of the Pembina Senior High School of Palembang, in the academic year of 2017/2018. It consisted of 147 students for 4 classes. In this research, the sample was two classes chosen through the cluster random sampling. One was treated as the experimental group and the other as the control group. After getting the two classes, the researcher did the individual random sampling by give a pretest to the students from the two classes as pretested and then matched based on their similar scores and got 25 pairs as sample. In research the researcher used the quasi experimental method with the randomized posttest-only control group design; the data were collected through the written test and were analyzed by using the percentage formula and t-test. Based on the result of the data analysis, it shows that the t-obtained was 4.547 and the t-critical value was 1.711 from degree of freedom (df) = 24. It means that the t-obtained was greater than the critical value or 4,547>1.711. It means the null hyporesearch was rejected and alternative hyporesearch was accepted. In conclusion, in was effective learning elliptical sentences through diagramming by the eleventh grade students of Pembina Senior High School of Palembang was effective.